PEMANFAATAN MINYAK BIJI KARET EPOKSI DAN PASIR KUARSA DALAM PEMBUATAN KARET GRIP HANDLE KENDARAAN BERMOTOR RODA DUA - Rahmaniar, Rahmaniar; Bondan, Aprillena Tornadez (Balai Riset dan Standardisasi Industri Palembang, 2017)
This study aimed to find a grip handle rubber compound formulations that meet the requirements of National Standard of Indonesia (SNI). This research used variety of plasticizes from epoxy of rubber seed oil and the filler variety of silica quartz sand. The research design used was completely randomized design (CRD) with two repetitions. The first factor was the epoxy of rubber seed oil concentration (A), respectively: A1 = 1 phr; A2 = 1.5 phr, and A3 = 2 phr. The second factor was the concentration of quartz sand with the particle size 200 mesh (B), respectively: B1 = 30 phr; B2 = 40 phr; B3 = 50 phr, and B4 = 60 phr. Quality testing for the characteristics of a rubber compoundÂ were tensile strength, elongation at break, tear resistance and density. The results showed that the value of the physical characteristics of the compound with the best treatment results were the treatment A1B2 (used 1 phr of rubber seed oil and 40 phr of silica quartz sand) with the value of tensile strength test results 77.98 kg/cm2, elongation at break 661%, tear resistance 34.1 kg/cm and density 1.24 g/ml. The test result of compound from of A1B2 treatment met the SNI 06-7031-2004 for grip handle.